Diagnostic significance of markers of inflammation in the cervical canal in pregnant women with bacterial vaginosis - T E Karapetian; N A Lomova; M I Kesova (IP Berlin A.V., 2018)
The aim of the study was to determine the proinflammatory and anti-inflammatory cytokines in the cervical canal as indicators of the state of local immunity in pregnant women with bacterial vaginosis (BV). Material and methods. The study included 45 pregnant women, who applied early in gestation. The main group consisted of 32 pregnant women, who had verified the diagnosis of BV, the comparison group - 13 pregnant women with normal vaginal microbiocenosis. In the mucus from the cervical canal, the content of pro-inflammatory cytokines (tumor necrosis factor a, interferon-g, interleukins - IL-1a, IL-2, IL-6, IL-8) and anti-inflammatory cytokines (IL-4, IL-10) was determined. Results. Local immunity before treatment of pregnant women with BV was characterized by a significant increase in the level of pro- and anti-inflammatory cytokines in relation to their production in pregnant women with normal vaginal microcenosis. After treatment with BV, cytokine levels were approaching those of healthy pregnant women, but the levels of tumor necrosis factor a and IL-8 changed little, which is probably due to the low production of these cytokines, since the leukocyte reaction in the epithelial vaginal locus is not expressed in vaginosis. The conclusion. Qualitative and quantitative changes in cytokine levels reflect the degree of activation of immunocompetent cells in any pathological process. The results obtained in this study reflect a certain autonomy of immune responses in the lower sections of the female genital tract.